Diagnostic accuracy of multiplex real-time PCR for detecting viruses associated with encephalitis: A systematic review and meta-analysis protocol - Sharifah Aliah Diyanah Syed Hussin; Xin Wee Chen; Hassanain Al-Talib; Ang-Lim Chua; Ziauddin Azimi; Seok Mui Wang (PLoS ONE, 2025)
Background Encephalitis is the most common infectious disease of the central nervous system and is associated with high morbidity, mortality, and disability. Therefore, rapid and accurate diagnosis is crucial to provide patients with timely and appropriate therapeutic intervention. In this study, a comprehensive systematic review with meta-analysis will be conducted to summarize the available data and evaluate the diagnostic accuracy of multiplex real-time polymerase chain reaction (PCR) in the detection of viral encephalitis. Methods We will search PubMed, MEDLINE, EMBASE, Web of Science (WoS), Scopus and Cochrane Library databases for studies evaluating the diagnostic accuracy of multiplex PCR for the diagnosis of encephalitis caused by viruses from January 2014 to December 2024. Observational study designs with full text will be exported and included. Risk of bias will be assessed using the Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) tool. Analyses will be performed using the “mada” package of R software (R Foundation for Statistical Computing, Vienna, Austria), and the Summary Receiver Operating Characteristic (SROC) will be calculated using the “midas” package of STATA version 15.0 (Stata Corp., College Station, TX, USA). Certainty of evidence will be performed using Grading of Recommendations Assessment, Development and Evaluation (GRADE) software. Results The results will provide clinical evidence for the diagnostic accuracy of the multiplex PCR assay for the detection of viruses that cause encephalitis, including sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), positive likelihood ratio (LR+), and negative likelihood ratio (LR-). Finally, we intent to submit this systematic review and meta-analysis to a peer-reviewed journal for publication. Conclusion This systematic review aims to provide current evidence for multiplex PCR assay for the diagnosis of viruses causing encephalitis. Importantly, this study focuses on the use of multiplex PCR for viral diagnosis and helps clinicians and patients to better understand its role in the diagnosis of CNS diseases. Systematic review registration PROSPERO registration number: CRD42023485942